2007
DOI: 10.1021/bp0700657
|View full text |Cite
|
Sign up to set email alerts
|

Production of Epigallocatechin Gallate 7-O-α-D-Glucopyranoside (EGCG-G1) Using the Glucosyltransferase from Leuconostoc mesenteroides

Abstract: Epigallocatechin gallate 7-O-alpha-D-glucopyranoside (EGCG-G1), as a novel compound with a higher water solubility and stability and similar antioxidant effect when compared with epigallocatechin gallate (EGCG), was produced from sucrose as a glucose donor and EGCG as a glucose acceptor by a glucosyltransferase from Leuconostoc mesenteroides. The pH and temperature for maximum EGCG-G1 production by the glucosyltransferase were 5.0 and 25 degrees C, respectively. The enzyme and substrates concentrations to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, their antioxidant activity remained unchanged or was slightly lower. Hyun et al further optimized the reaction conditions for the synthesis of EGCG-G1 using glucansucrase of L. mesenteroides B-1299CB as catalyst, achieving a conversion efficiency of 67% under optimized conditions (Hyun et al 2007). Glucansucrase of L. mesenteroides B-1299CB was also demonstrated to glucosylate quercetin with the production of α-D-glucopyranosyl-4′-O-quercetin and α-D-glucopyranosyl-3′-O-quercetin (Figure 7), whose solubility in water were significantly improved ).…”
Section: Glucosylation Of Flavonoids By Glucansucrasesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their antioxidant activity remained unchanged or was slightly lower. Hyun et al further optimized the reaction conditions for the synthesis of EGCG-G1 using glucansucrase of L. mesenteroides B-1299CB as catalyst, achieving a conversion efficiency of 67% under optimized conditions (Hyun et al 2007). Glucansucrase of L. mesenteroides B-1299CB was also demonstrated to glucosylate quercetin with the production of α-D-glucopyranosyl-4′-O-quercetin and α-D-glucopyranosyl-3′-O-quercetin (Figure 7), whose solubility in water were significantly improved ).…”
Section: Glucosylation Of Flavonoids By Glucansucrasesmentioning
confidence: 99%
“…However, glucansucrases were also capable of glucosylating the hydroxyl group on the A ring of flavonoids (hydroxyl group at position 7). Hyun et al, showed that the glucansucrase of L. mesenteroides B-1299CB used EGCG as the acceptor subs t r a t e t o c a t a l y z e t h e s y n t h e s i s o f α-D-glucopyranosyl-7-O-EGCG with a conversion degree of 67% (Hyun et al 2007). GtfR of S. oralis was reported to specifically attach a glucosyl moiety to the flavanone compound taxifolin at the para position (O4') of the B ring while it transferred a glucosyl moiety to the C7 hydroxyl group of the A ring of isoflavones (Overwin et al 2016).…”
Section: Glucosylation Of Flavonoids By Glucansucrasesmentioning
confidence: 99%
“…The acceptor reaction mediated by L. mesenteroides glucosyltransferase and purification of EGCG-G1 using Sephadex LH-20 chromatography were performed as described previously [9,19].…”
Section: Preparation Of Egcg-g1mentioning
confidence: 99%
“…In comparison, the glucosylated flavanol gallates exhibit similar antioxidant properties, yet have increased solubility in water and stronger tyrosinase inhibitory effects, suggesting that these forms may be superior to flavanol gallates aglycones for application as food additives, drugs, and cosmetics ( Moon et al, 2006 ; Zhang et al, 2016 ). To date, glycosylation of flavan-3-ols gallates have often been carried out via chemical conversion or use of glycosyltransferases of bacterial origin ( Kitao et al, 1995 ; Moon et al, 2006 ; Hyun et al, 2007 ; Zhang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%